English as a lingua franca in interpreting and translation: a survey of practitioners - Albl-Mikasa, Michaela; Ehrensberger-Dow, Maureen; Gieshoff, Anne Catherine; Hunziker Heeb, Andrea (Frontiers in Communication, 2024)
Over the last few decades, the English language has become prevalent throughout the world in the domains of international diplomacy, business, research, and technology and is becoming increasingly important in many other areas. Much research into the use of English as a lingua franca has focused on its role in fostering communication across linguistic and cultural boundaries. Recently, however, concerns have been raised about the additional cognitive load that having to function in a non-native language can place on interlocutors. In an international survey, 883 professional language mediators (i.e., translators, conference interpreters, and community interpreters) provided details about their experiences dealing with the English produced by native vs. non-native speakers and identified features and difficulties associated with processing the respective input as well as their coping strategies. Although they acknowledged that both native and non-native speakers produce English that is difficult to deal with, the language mediators largely agreed that the latter were much more likely to do so, with vocabulary use, word choices, and sentence structures identified as particularly problematic. The main coping strategies for all three groups were to really concentrate on the message being conveyed, try to improve the formulation of it for the target audience, and intervene in the communication situation for clarification if possible. Self-regulation and reliance on information external to the situation were also mentioned as very important. Although almost half of the participants said that they preferred to work with native speaker produced output, many expressed no preference. The study results have important implications for various situations involving non-native speakers of the language being used for communication.